A series of four cases on plasmablastic lymphoma: A rare Epstein–Barr virus-positive lymphoma in immunocompetent patients with varied presentation (Indian Journal of Case Reports, 2020)
Plasmablastic lymphoma (PBL) is a rare and aggressive type of non-Hodgkin lymphoma (NHL) which is typically seen in the setting of an immunocompromised state, classically associated with human immunodeficiency virus infection. It is often also associated with Epstein–Barr virus infection. It has an immunophenotype of a terminally differentiated B lymphocyte. The diagnosis of PBL is challenging due to complex overlap with myeloma and other B-cell NHL having a plasmablastic morphology. In the past few years, there are an increasing number of cases being identified in patients with no known immunocompromised state. We hereby report a case series of four such cases in immunocompetent patients with different sites of involvement and varied presentation to add to the literature.